SPATIAL PATTERNS OF BACTERIAL SIGNATURE BIOMARKERS IN MARINE SEDIMENTS OF THE GULF OF MEXICO - Li Y.-L.; Zhang C.L.; Peacock A.D.; White D.C.; Geyer R. (My University, 2007)
Sediment cores near a cold methane seep and gas hydrates in the Gulf of Mexico were analyzed for bacterial membrane phospholipid fatty acids (PLFA) and isoprenoid quinones. Nearby non-seep marine sediments were also analyzed for the purpose of comparison. Our goal was to use these biomarkers as proxies for microbial community structure and redox indicators. Total PLFA varied from core to core and were significantly less abundant in non-seep marine sediments than those near the cold seep or gas hydrates. In general, saturated straight chain, terminal branched and mid-chain branched, and monounsaturated fatty acids contributed > 98% of the total PLFA. The branched fatty acids (i.e., aC15:0, iC15:0, Me10C16:0) could be largely attributed to sulfate-reducing bacteria and the monounsaturated fatty acid (i.e., 16:1ω7c and 18:1ω7c) could be attributed to sulfide-oxidizing bacteria (Beggiatoa/Thioploca). Principal component analysis of PLFA data revealed that microbial communities were consistent with the spatial distributions of gas hydrates and Beggiatoa mats and with the variation in geochemical conditions. Isoprenoid quinone profiles indicated that aerobic respiration was the dominant metabolic process in the top-most sediment layers while the anaerobic respiration dominated the deeper intervals in the marine sediments. Significant amount of cyclopropyl fatty acids at all sites indicated the stress adaptation of the bacteria in the extreme environment. The consistency between the distribution of PLFA and respiratory quinones and the variation in geochemical conditions suggested that analyses of PLFA and quinone could help us to locate the existence of the coupled sulfide-oxidization and sulfate-reduction processes.
Keywords: BIOMARKER; GAS HYDRATE; GULF OF MEXICO; MULTIVARIATE STATISTICS; PHOSPHOLIPID FATTY ACIDS; RESPIRATORY QUINONES; TRANS/CIS RATIO